The Macroeconomics of Scaling Up Aid : Lessons from Recent Experience - Berg, Andrew (Occasional Papers; Occasional Paper, 2007)
This study analyzes key issues associated with large increases in aid, including absorptive capacity, Dutch disease, and inflation. The authors develop a framework that emphasizes the different roles of monetary and fiscal policy and apply it to the recent experience of five countries: Ethiopia, Ghana, Mozambique, Tanzania, and Uganda. These countries have often found it difficult to coordinate monetary and fiscal policy in the face of conflicting objectives, notably to spend the aid money on domestic goods and to avoid excessive exchange rate appreciation.